Catalyst in Basic Oleochemicals - Eva Suyenty; Herlina Sentosa; Mariani Agustine; Sandy Anwar; Abun Lie; Erwin Sutanto (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2007)
Currently Indonesia is the world largest palm oil producer with production volume reaching 16 million tones per annum. The high crude oil and ethylene prices in the last 3 – 4 years contribute to the healthy demand growth for basic oleochemicals: fatty acids and fatty alcohols. Oleochemicals are starting to replace crude oil derived products in various applications. As widely practiced in petrochemical industry, catalyst plays a very important role in the production of basic oleochemicals. Catalytic reactions are abound in the production of oleochemicals: Nickel based catalysts are used in the hydrogenation of unsaturated fatty acids; sodium methylate catalyst in the transesterification of triglycerides; sulfonic based polystyrene resin catalyst in esterification of fatty acids; and copper chromite/copper zinc catalyst in the high pressure hydrogenation of methyl esters or fatty acids to produce fatty alcohols. To maintain long catalyst life, it is crucial to ensure the absence of catalyst poisons and inhibitors in the feed. The preparation methods of nickel and copper chromite catalysts are as follows: precipitation, filtration, drying, and calcinations. Sodium methylate is derived from direct reaction of sodium metal and methanol under inert gas. The sulfonic based polystyrene resin is derived from sulfonation of polystyrene crosslinked with di-vinyl-benzene. © 2007 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)